MENGHUBUNGKAN DESAIN ORGANISASI DENGAN EFEKTIVITAS PENGELOLAAN SUMBER DAYA MANUSIA DAN PROSES BISNIS DALAM KONTEKS LEMBAGA KEUANGAN, SOSIAL, DAN KESEHATAN (STUDI PADA BANK INDONESIA, RUMAH ZAKAT, DAN PELAYANAN KESEHATAN RS) - Yulianatasia Simanjuntak; Rajin Rajin; Apriyani Sinen; Ronny Edward Utama (Taksasila Edukasi Insani, 2026)
This study aims to analyze the relationship between organizational design and the effectiveness of human resource management (HRM) and business processes across three strategic sectors: finance (Bank Indonesia), social (Rumah Zakat), and healthcare (hospital services). This research employs a qualitative descriptive method using literature review and case study approaches. The findings indicate that an appropriate organizational design significantly influences the improvement of employee performance, business process efficiency, and overall organizational effectiveness. Bank Indonesia implements a functional and digitally adaptive organizational structure that strengthens policy coordination and enhances employee productivity. Rumah Zakat adopts a hybrid organizational design emphasizing flexibility, cross-functional collaboration, and social values, which improve staff performance and program transparency. Meanwhile, healthcare organizations apply a service-unit and multidisciplinary team-based structure that enhances interprofessional coordination and the quality of patient services. Therefore, the alignment between organizational design, human resource strategy, and business processes is proven to be a key determinant in achieving organizational effectiveness and competitiveness across different sectors. Keywords : business processes, financial–social–health institutions, human resource management, organizational design, organizational effectiveness